AN ANALYSIS OF THREE ENGLISH TEXTBOOKS FOR ELEVENTH GRADE OF SENIOR HIGH SCHOOL - Nursakina Husen; RR Hasti Robiasih; Imam Ghozali (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
The objectives of this study were to: (1) see whether the textbooks used for learning English meet the criteria of a good textbook and (2) reveal the strengths and weaknesses of the textbook. This research was conducted using content analysis because the data were collected from textbooks. Observation data through and document analysis. The data were analyzed through qualitative research. The object of this research is the English textbook used for class XI SMA students. The results of the study found that English to stop bullying currently fulfills the twelve criteria of a good textbook by Mukundan containing 1) Books related to syllabus and curriculum, 2) Methodology, 3) Suitability with students, 4) Physical and utilitarian attributes, and 5 ) Efficient spending of complementary materials, 6) General, 7) Speaking, 8) Reading, 9) Writing, 10) Vocabulary, 11) Grammar, and 12). Sports. Furthermore, the study also found that the advantages of English in relation to current bullying are providing appropriate communicative activities with students, providing teachers' books, and samples of material that are familiar to students. Meanwhile, the weakness of this textbook is that it does not provide assignments to develop students' listening and pronunciation skills. Also, the text and images are not up-to-date.